SELEKSI GUDANG DISTRIBUSI PADA RANTAI PASOK PELUMAS MENGGUNAKAN MULTI CRITERIA DECISION MAKING - Kurniawan Agung Susanto; Sawarni Hasibuan (Operations Excellence: Journal of Applied Industrial Engineering, 2018)
High competition in the lubricants business results in customer services become a benchmark for the success of this business in Indonesia, One of the services provided is pegudangan system that is part of the supply chain system. The existence of obstacles in the process of handling in and out in a warehouse handling PT Petronas Niaga Indonesia resulted in the need for companies to choose a new warehouse as an alternative lubricants. The number of alternatives which can be used warehouse forced the company to make the process of pre-qualification and qualification process to obtain alternative lubricants warehouse priority desired by the company. In the pre-qualification process lubricants warehouse alternative screening process is done by using the weighted product method to reduce warehouse alternative lubricants in the process of qualifying criteria based lubricants warehouse needs. In the process of qualifying the selection process is then performed by Analytical method Hirarchy Process (AHP) using five criteria: cost, infrastructure, market, safety, and the macro environment. Each of these criteria are translated into sub-criteria. The results obtained qualification process priority is the best lubricant warehouse is PT GAC Samudra Logistics with the highest weight, followed by PT Wiraswasta Gemilang Indonesia and PT Jaya Puninar with weights respectively and PT GAC Samudra Logistics superior in infrastructure and safety criteria, while PT Wiraswasta Gemilang Indonesia superior at cost and market criteria.